JOB STRESS AND EMPLOYEE PERFORMANCE AMONG ACADEMIC STAFF IN UNIVERSITY OF BENIN, EDO STATE (Journal of Global Accounting, 2025)
This study examined the relationship between job stress and employee performance among academic staff in University of Benin, Benin City, Edo State, Nigeria. Using a quantitative survey design, survey data from 407 respondents revealed that excessive workload, poor interpersonal relationships, and inadequate organizational support significantly contribute to job stress. Employees reported feeling overwhelmed, struggling with work-life balance, and lacking sufficient resources to perform effectively. Regression analysis confirmed a strong negative correlation between job stress and performance (β = 0.83, p < 0.001). The findings highlight the need for institutional interventions, such as workload management, conflict resolution programs, and enhanced organizational support, to mitigate stress and improve productivity. This research provides valuable insights for university administrators and policymakers to foster a healthier work environment and optimize employee performance in higher education settings.
Keywords: Academic Staff; Employee Performance; Job Stress; Organizational Support; Workload